Myristoylation: An Important Protein Modification in the Immune Response - Udenwobele, Daniel Ikenna; Su, Ruey-Chyi; Good, Sara V.; Ball, Terry Blake; Varma Shrivastav, Shailly; Shrivastav, Anuraag (Frontiers in Immunology, 2017)
Increasing biochemical and genetic evidence confirms that myristoylation is an evolutionary conserved process of lipid modification in many eukaryotic and viral proteins. The discovery that the N-terminal blocking group of cyclic AMP-dependent protein kinase is a myristic acid, some 33 years ago, led to the birth of the field of ‘myristoylation’, dedicated to understanding the significance of protein myristoylation. Although the field is in its infancy, an increasing number of studies have appeared addressing the mechanisms and significance of N-myristoylation in various aspects of cellular signaling. N-Myristoylation is known to occur in mammalian, plant, viral and fungal proteins. Many proteins involved in a variety of signal cascades and cellular differentiation are myristoylated. These include the catalytic subunit of cAMP-dependent protein kinase, the β-subunit of calcineurin, the α-subunit of several G-proteins, the cellular and transforming forms of pp60src. Given the indispensible role of myristoylation in cellular functions, in this review, we examine the myriad functional implications of myristoylation with respect to immune function and regulation.